Repairing public trust through communication in health crises: A systematic review of the literature - Liu, Y.; Duarte, H. (Public Management Review, 2025)
Public trust repair is a particularly important issue in public administration during public crises. Taking health crises as the context and trust repair as a lens, we systematically reviewed existing research to provide comprehensive insights into how public trust can be rebuilt through communication. From this, we identified five categories of trust-repairing communication strategies and integrated a framework by discussing the communication elements those strategies involved. Moreover, we conducted a critical analysis of how these communication strategies help build trust through the six trust-repair mechanisms put forward by Bachmann, Gillespie, and Priem (2015).